Atrial Fibrillation and Malignancy: The Clinical Performance of Non–Vitamin K Oral Anticoagulants—A Systematic Review - Russo, Vincenzo; Bottino, Roberta; Rago, Anna; Micco, Pierpaolo Di; D' Onofrio, Antonio; Liccardo, Biagio; Golino, Paolo; Nigro, Gerardo (Seminars in Thrombosis and Hemostasis, 2019)
Atrial fibrillation (AF) is commonly diagnosed in the setting of active cancer. Because of an increased risk of either thromboembolic events or bleeding, the decision to initiate therapeutic anticoagulation in patients with active cancer can be challenging. Moreover, little is still known about the optimal anticoagulation therapy in the setting of AF and cancer, and no guidelines are as yet available. Considering that nonvitamin K antagonist oral anticoagulants (NOACs) are recommended as alternatives to vitamin K antagonists for stroke prevention in AF patients with CHA2DS2-VASc score ≥2, the authors performed a systematic review of the current literature to describe the efficacy and safety of NOACs in AF patients with malignancy.
Keywords: atrial fibrillation; cancer; NOACs; dabigatran; apixaban; rivaroxaban; edoxaban; bleeding; stroke; embolism